(Pre)association as a crucial step for computational prediction and analysis of the catalytic activity of σ-hole donating organocatalysts. Issue 1 (24th November 2022) - Polonnikov, Denis A.; Il'in, Mikhail V.; Safinskaya, Yana V.; Aliyarova, Irina S.; Novikov, Alexander S.; Bolotin, Dmitrii S.
Abstract : A suitable model for computational study giving reliable estimation of the catalytic effect of σ-hole donating organocatalysts is suggested. Abstract : Based upon the experimentally obtained kinetic data on iodonium salt catalyzed nucleophilic addition of isocyanide to imine leading to imidazopyridine species, a reliable model for DFT calculations has been suggested. It was shown that preassociation of the catalysts with the reaction species might significantly affect the total energy profile of the reaction obtained by DFT. The associates of the organocatalysts featuring the solvent molecules ligated to its σ-holes should be used as a starting point for calculations. Taking these reaction steps into consideration during the calculations leads to significantly more reliable theoretical results, which can be applied either for prediction of the catalytic activity of yet untested species or for justification of the catalytic paths based upon the experimental kinetic data as well.